Riscos e perigos: um estudo sobre os conflitos cotidianos dos agenciadores do tráfico de drogas ilícitas - Santiago Neto, João Pedro de (2014)
This dissertation is to develop an objective analysis of the phenomenon of drug trafficking from the ethnographic understanding of the meanings of situations experienced by individuals who practice the trade / crack /, marijuana and cocaine in Fortaleza, Ceará. We intend to analyze the information obtained during eight months of / interaction / with youth involved in various practices / deviant / (Becker, 2008). Based on ethnographic records on everyday streets, squares, alleys and peripheral land the city we seek to understand the logic that permeate the inherent dynamics of the drug trade conflicts. For this, situations that help to understand the views of practitioners of retail drug will be presented. It is noteworthy reports of traffickers on gains, threats and dilemmas experienced in the context of socially reprehensible practices. The ethnographic data express and reflect the ways they relate different logics of action in the landscape of trafficking. In this sense, we present some of the strategies of trafficking, such as assaults and cover-up of negotiations with the police, which were aimed at the dribble of punitive measures and strengthening / deviant / practices.